Ethnolinguistics and Lexical Contact between Spanish and Mapudungun for an Intercultural Territory (London Journal of Research In Humanities and Social Sciences, 2025)
This paper describes the research of Dr. Gilberto Snchez Cabezas and his importance in the lexical aspect of Spanish-Mapudungun contact in Chilean territory. This Mapuche language scholar is relevant today due to his reconsideration of Rodolfo Lenz's ideas and the life experiences linked to the quality and authenticity of his academic work, which contribute to a genuine recognition of the connection between culture and language within the discipline of ethnolinguistics. The author is not only important in the field of linguistics, but his approaches are also linked to interculturality for the territory and one of the most relevant ways of transforming our society: education.
Keywords: identity; sign; literary semiotics; Trauma; posttraumatic stress disorder; Professional development; Contract Faculty; Recognition Disparities; Job Security; Teaching Load.; ChatGPT; AI-based writing assistant; learner perceptions; Saudi EFL context; automated feedback; historical linguistics; Old English; Irregular Verbs; language; Culture; interculturality; Mapudungun; Contact; Lexicon